Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2003
DOI: 10.1063/1.1601688
|View full text |Cite
|
Sign up to set email alerts
|

Jones matrix method for predicting and optimizing the optical modulation properties of a liquid-crystal display

Abstract: We present a simple technique for the calibration, prediction, and optimization of the optical modulation properties of a liquid-crystal display (LCD). The method is useful when there is no information about the internal fabrication parameters of the device (the orientation of liquid-crystal molecules, the twist angle, or the birefringence of the material). A complete determination of the LCD Jones matrix is accomplished by means of seven irradiance measurements for a single wavelength. This technique only req… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
87
0
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(90 citation statements)
references
References 22 publications
0
87
0
3
Order By: Relevance
“…A general expression for the total phase  of a LCD inserted between two polarizers (whose orientations are  1 and  2 respectively) is provided in Ref. (Moreno et al, 2003):…”
Section: Mueller To Jones Conversion: Phase Predictionmentioning
confidence: 99%
See 1 more Smart Citation
“…A general expression for the total phase  of a LCD inserted between two polarizers (whose orientations are  1 and  2 respectively) is provided in Ref. (Moreno et al, 2003):…”
Section: Mueller To Jones Conversion: Phase Predictionmentioning
confidence: 99%
“…We follow the technique proposed in Ref. (Moreno et al, 2003), being suitable to predict the phase response in LCDs. This technique considers that any non-absorbing reciprocal polarization device can be described by an unimodular unitary Jones matrix (Fernández-Pousa et al, 2000), the TNLCoS displays being a particular case.…”
Section: Mueller To Jones Conversion: Phase Predictionmentioning
confidence: 99%
“…17 to describe this profile. This model provides very accurate calculations of amplitude and phase modulation provided by LCDs [18][19][20] .…”
Section: Transmissive Lcdsmentioning
confidence: 99%
“…A series of reverse engineering models, based on the Jones matrix formalism for polarized light, have been proposed [15][16][17] to describe the modulation of the anisotropic properties of the LC layer as a function of the applied voltage. Other approaches consider the LCD as a black box and concentrate on the numerical evaluation of the matrix elements of the Jones matrix describing the LCD 18 . Among the reverse engineering models, the one proposed in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…The goal of this study is to determine the signs as well as the absolute values of the matrix elements can be determined by polarimetric methods experimentally, but it has been thought that the signs of the elements can not be determined uniquely by polarimetric methods only. However it has been shown that the signs can be determined by polarimetric methods [11].…”
Section: Introductionmentioning
confidence: 99%